Enhancing learner self-monitoring in self-assessment through the use of pedagogical resources - Kothar Talib Sulaiman Al Harrasi (Cogent Social Sciences, 2024)
AbstractThe increased emphasis on self-directed learning has sparked significant interest in self-assessment (SA) within essay writing over recent decades. While prior research has predominantly examined the role of instructional tools like rubrics and checklists in guiding learners through the SA process, this study seeks to delve deeper into the various factors that might impact the utilization of these tools. Specifically conducted in a higher education (HE) setting, this study aimed to comprehend how pedagogical resources for SA are perceived, put into practice, and evolved by both students and educators, thereby offering insights into enhancing learner self-monitoring. The findings revealed that students effectively engaged in SA when utilizing criterion-referenced pedagogical aids, comprehending their application, receiving teacher support, and acknowledging the significance of SA. These outcomes underscore the necessity of addressing all these influences comprehensively to empower students in conducting autonomous self-assessment.